2021
DOI: 10.3389/fnagi.2021.682908
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Atherosclerotic Calcification Characteristics Relate to Post-stroke Cognitive Impairment

Abstract: Background: Together with cerebral small vessel disease (CSVD), large vessel atherosclerosis is considered to be an equally important risk factor in the progression of vascular cognitive impairment. This article aims to investigate whether carotid atherosclerotic calcification is associated with the increased risk of post-stroke cognitive impairment (PSCI).Methods: A total of 128 patients (mean age: 62.1 ± 12.2 years, 37 women) suffering from ischemic stroke underwent brain/neck computer tomography angiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Our previous study found that fibrinogen was an independent risk factor for WMH in patients with CADASIL, but this correlation was not obvious in patients with sporadic CSVD (Guo et al, 2021). To date, studies examining blood biomarkers of VCI have mainly focused on vascular endothelial dysfunction and have been limited to a certain type of disease, such as CSVD or stroke (Zhu et al, 2019;Wang Y. et al, 2021). The detection of relevant blood biomarkers may be more persuasive and have greater predictive value when the heterogeneity of stroke lesion distribution in neural circuits is accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study found that fibrinogen was an independent risk factor for WMH in patients with CADASIL, but this correlation was not obvious in patients with sporadic CSVD (Guo et al, 2021). To date, studies examining blood biomarkers of VCI have mainly focused on vascular endothelial dysfunction and have been limited to a certain type of disease, such as CSVD or stroke (Zhu et al, 2019;Wang Y. et al, 2021). The detection of relevant blood biomarkers may be more persuasive and have greater predictive value when the heterogeneity of stroke lesion distribution in neural circuits is accounted for.…”
Section: Introductionmentioning
confidence: 99%